(3JMQjQ cJGH eCNhPGJ GQTejOSs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI NeSI YTQ TcdkG bGd GdGSJGP GdeNJU gPg ebGdI efShHI Edi CQTejOS efgG CTcGd NeSI bdjdI GdYOO cKjQI GdahGFO aj CUhd GdgfOSI s
(3BNQgG (B:s
(3hCbhd Cf (B85 (3ebShe Ydi fSHI PGJ hSW WQajf Ydi (B4 (3, hbSeI GdGWhd (B45 (3hPdc dGf (B45 (3hJQ GdSOS s
(3Vef eLehY , JQJjHgG (B: 10s
(3HgG fXGe GdJYbjHIs
(3JQLeI GHf bQIs
(3JaSjQ GHh GdMSf GdfShjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs